Perbedaan tingkat pemahaman haid dan istihadlah sebelum dan sesudah dilakukan pembelajaran kitab uyunul masail linnisa' pada santri di asrama pelajar islam pondok pesantren syubbanul wathon tegalrejo giri secang magelang - Aisyah Nur, nisaa; Arini, Aida; Ilahiyah, Iva Inayatul; Nur Salim, Mohamad (PAI FAI UNHASY Tebuireng Jombang, 2025)
Santri who stay at the Islamic Student Dormitory of Syubbanul Wathon Tegalrejo Islamic Boarding School have different educational backgrounds that previously had no learning about menstruation in detail, some did not understand because at the previous formal education level it was not taught. This research was used to find out: 1. The level of understanding before learning Kitab Uyunul Masail Linnisa' on students in the Islamic Students Dormitory of Syubbanul Wathon Tegalrejo Islamic Boarding School, 2. The level of understanding after learning Kitab Uyunul Masail Linnisa' on students in the Islamic Students Dormitory of Syubbanul Wathon Tegalrejo Islamic Boarding School, 3. The difference in the average value of the level of understanding of menstruation and istihadlah before and after learning Kitab Uyunul Masail Linnisa' on students in the Islamic Students Dormitory of Syubbanul Wathon Tegalrejo Islamic Boarding School. This study used a quantitative approach, experimental research based on the One-Group Pretest-Posttest Design paradigm, with 34 respondents, using simple random sampling technique. Data collection techniques are: observation, tests, documentation. Data analysis techniques used to answer problem formulations number 1 and 2 using descriptive statistics, number 3 using non-parametric analysis, namely Wilcoxon. The results showed that: 1. The level of understanding before learning Kitab Uyunul Masail Linnisa' on students in the Islamic Student Dormitory of Syubbanul Wathon Tegalrejo Islamic Boarding School shows, from a total of 34 respondents, the average value of the level of understanding before learning is 31.91 and the standard deviation value is 15.393. 2. The level of understanding after Kitab Uyunul Masail Linnisa' on students in the Islamic Students Dormitory of Syubbanul Wathon Tegalrejo Islamic Boarding School shows, out of 34 respondents get an average value of the level of understanding after learning 95.68 and a standard deviation value of 5.639, 3. There is a difference in the average value of the level of understanding of menstruation and istihadlah before and after Kitab Uyunul Masail Linnisa' on students in the Islamic Students Dormitory of Syubbanul Wathon Tegalrejo Islamic Boarding School.